Effect of metal ions on amylase production - Jha, Sangeeta; Rai, Himadri; Chattopadhyay, Richa; Kaur, Veer Pal; Indupriya, M; Shanti, V (Recent Research in Science and Technology, 2013)
Amylase producing fungi were isolated from different soil samples. About 11 fungal isolates were isolated which were screened for Amylase production on starch agar medium using iodine test. Of the 11 isolates, three isolates showed clear zones and the isolate showing maximum clearance zone was selected for further studies. Identification of isolate showed that it belonged to Genus Aspergillus. The effect of different metal ions on the production and activity of Amylase was studied. Five different ions were used for the study. Starch agar medium was prepared with different metal ions and inoculated with the culture and incubated. It was seen that maximum mycelial growth was observed with MgSO4 followed by KNO3 but very less or negligible growth was seen when grown with CaCO3. Therefore, Mg ions were considered to be the best ion for optimum growth of the fungus and thus considered the best inducer for Amylase production as maximum enzyme activity was observed with Mg ions but Ca and Cu ions showed less activity and therefore might be showing inhibitory effect on Amylase production.